Magtstatens transformationer. En begrebshistorisk og historiografisk undersøgelse - Olden-Jørgensen, Sebastian (Historisk Tidsskrift, 2013)
The Transformations of the "Power State" (Machtstaat): The History of an Historiographical and Political ConceptThe concept of the “power state” (Machtstaat) was introduced into Danish historiography in 1983/85 by Leon Jespersen as a concept “implying some of the elements present in a militarized state and in a tax state with increased expenditure on defence, administration, the court and diplomacy, a state which had also been strengthened partly for reasons of prestige” (Scandinavian Journal of History 1985, p. 272, cf. footnote 72 above). This rather broad definition was narrowed down by Knud J.V. Jespersen who in 1989 defined the power state as “a state existing by virtue of itself, outside and above the social classes. This type of government was an innovation of Renaissance Europe, caused especially by a new, expensive technology of war that forced the states to operate as organizers of substantially increased armies” (Jespersen: Danmarks Historie, p. 18, cf. footnote 79 above).Even if the power state turns up occasionally in recent Scandinavian scholarship, the concept is normally used neither in the broad meaning defined by Leon Jespersen nor as conceived more succinctly by Knud J.V. Jespersen, but in a diffuse manner indicating a military state or merely a strong government. This development seems awkward for a concept that was introduced and refined in order to define a new research paradigm. An analysis of its historical roots, that may uncover inherent difficulties or contradictions, is thus called for.According to Leon Jespersen the concept of the power state is derived from the so-called Prussian school of historiography and political science, represented by scholars such as Carl von Clausewitz, Heinrich von Treitschke, Carl Schmitt and Otto Hintze. Of these, only Hintze actually used the concept of the Machtstaat, and only once, in an influential article on the origins of the modern state from 1931. However, the concept of the Machtstaat can be traced further back. Already in 1868 the Swiss cultural historian Jacob Burckhardt used the word in a lecture to stigmatize the dreadful expansionist policy of Louis XIV. To Burckhardt the Machtstaat was a state that claimed full possession - body and soul - of its subjects and used liberty, prosperity and culture only as a front for the raw pursuit of power. A similar if not identical usage can be documented among German jurists contrasting the Machtstaat to the Rechtstaat (a state governed by the law). Among German political historians, however, the attitude toward power was much more positive. From 1906 (Friedrich Meinecke) until the 1950s (Gerhard Oestreich) the concept of the Machtstaat figured regularly in the writings of the so-called Borussian (Prussian) school. To these historians the word implied much more than a significant amount of power. It pointed to a greater truth: that the essence of the state was power and that the pursuit of power was the highest duty of the sovereign. The background for their enthusiasm was twofold. On the one hand, German idealism, with its basis in Hegel and Romanticism, tended to see states not as conglomerates of classes, elites and political interests, but as spiritual entities endowed with true individuality and purpose. On the other hand, the historical experience of the Reichsgründung (the German unification culminating in the victory over France and the creation of the German Empire in 1871) had taught the lesson that German unity was achieved not by means of Liberalism and popular sovereignty but rather through Prussian military strength and power politics. According to this philosophy of history, the military might, cunning and brutality associated with Prussian history and the house of Hohenzollern was redeemed by Prussia’s deutscher Beruf (German calling) to become a Machtstaat in order to ultimately realize German unity.This historiographical background adds perspective to the concept of the power state. In Leon Jespersen’s version it is simply too broad and should be replaced by more operational concepts such as the military-fiscal state. Knud J.V. Jespersen’s version of the power state actually has much in common with the Machtstaat of the Borussian historians. First and foremost, they share the idea of an autonomous state which exists for its own purpose and not as a vehicle for group interests. Secondly, they have in common a penchant for teleology, even though the - implicit - goal of Knud J.V. Jespersen’s power state is not national destiny, but modernization. It seems, nevertheless, that in order to be logically coherent, and hence persuasive, Knud J. V. Jespersen’s power state does indeed presuppose an explicit philosophical (Hegelian) idealism and modernization theory, both of which it obviously lacks. Perhaps this is the reason why it has had only a limited impact. The simple conceptual framework of modern and early modern has been preferred by the scholarly community because these terms more readily facilitate the discussion of modernization and statebuilding and their mutual relationship.